Population ecology of feral horses in an era of fertility control management - Ransom, Jason Ian, author; Hobbs, N. Thompson, advisor; Baker, Dan, committee member; Boone, Randall, committee member; Bruemmer, Jason, committee member (Colorado State University. Libraries, 2012)
Management of wildlife often requires intervention to regulate growth of populations that would otherwise become overabundant. Controlling fecundity using contraceptives has become an increasingly popular tool for attempting to manage locally overabundant wildlife species, but the population-level effects of such applications are largely unknown. Contraceptive treatments can produce unexpected feedbacks that act on births, survival, immigration, and emigration. Such feedbacks may considerably influence our ability to regulate populations using fertility control. I followed feral horses (Equus caballus) in three intensively managed populations to assess longitudinal treatment effects on demography. The transient contraceptive porcine zona pellucida (PZP) produced longer duration of infertility than intended. Repeated PZP vaccinations of females extended the duration of infertility far beyond the targeted management period, with time to first post-treatment parturition increasing 411days for every annual inoculation received. When these animals did conceive and give birth, parturition was later in the year and temporally asynchronous with forage abundance. An average of 30% (range=11-77%) of females were contracepted annually during the treatment period in all three populations and apparent annual population growth rate was 4-9% lower in the post-treatment years as compared to pretreatment years. Population growth was positive, however, and increased steadily every year that a management removal did not occur. The observed number of births was 33% fewer than the expected number of births, based on number of treated females, individual efficacy of treatment, and number of untreated females and their age-specific fecundity rates. Only half of this difference was explained by the apparent residual effect of treatment. Birth rate in the youngest untreated females (age 2-5 years old) was reduced in years when their conspecifics were treated, enhancing the effects of treatment at the population-level. This was partially offset by increased survival in adults, including a 300% increase in presence of horses >20 years old during the post-treatment period. In closed populations of feral horses, the positive feedbacks appear to outweigh the negative feedbacks and generate a larger contraceptive effect than the sum of individual treatments. The role of fertility control is uncertain for open populations of many wildlife species, with broad consensus across a synthesis of research that negative feedbacks on fertility control performance are occurring, and in many cases increased survival and increased immigration can compensate entirely for the reduction in births attributed to treatment. Understanding species' life-history strategies, biology, behavioral ecology, and ecological context is critical to developing realistic expectations of regulating wildlife populations using fertility control.
Keywords: fertility control; horse; population dynamics; population ecology; wildlife contraception; Equus